Policy implementation and citizens’ participation: a lesson from the 2022 redesigning of naira note in Nigeria - Fajonyomi, Sylvester Olubanji; Ajulor , Omoniyi Victor; Ibikunle, Busayo Qazeem; Eweje, Adeniyi Olamide (Journal of Social Sciences and Management Studies, 2025)
Policy implementation remains one of the major sources of policy failure in developing nations, particularly where citizen participation is weak. Nigeria’s 2022 Naira redesign policy illustrates this challenge, as the redesign of the ₦200, ₦500, and ₦1000 notes generated severe socio-economic hardship and widespread resistance. This study examines the implementation process of the 2022 Naira redesign policy, focusing on citizen participation and the implications for public wellbeing. Using an exploratory research design based on secondary data, documentary evidence, and recent empirical analyses, the study identifies key implementation failures, including inadequate public sensitisation, limited circulation of the redesigned notes, and the simultaneous introduction of other monetary policies such as cash-withdrawal limits and the cashless policy. Findings reveal that citizens were largely excluded from decision-making and poorly prepared for behavioural adjustments required by the policy, resulting in violent protests, economic losses, reduced access to cash, and disruptions to business and household welfare. The study contributes new insights by demonstrating how insufficient citizen engagement and rapid policy rollout can transform a well-intentioned monetary reform into a socially destabilising measure. It recommends phased implementation, stronger public communication, expanded digital-payment literacy, and early circulation of redesigned notes before withdrawing old currency. Ensuring meaningful citizen participation is essential for enhancing policy legitimacy and safeguarding national wellbeing.